P1-S6.42 HPV vaccine and sexual behaviour among US adolescent and young adult women. (10th July 2011) - Liddon, N; Leichliter, J S; Hood, J; Markowitz, L E
Abstract : Background: Monitoring HPV vaccine uptake can identify potential disparities in coverage and guide vaccine implementation efforts. While there are several national estimates of HPV vaccine uptake among US women, there are few data on vaccination status in relation to sexual behaviour. We analysed receipt of HPV vaccine and intent to get vaccinated by demographic and sexual behaviour data from a nationally representative US survey. Methods: In 2007–2008, 1243 females aged 15–24 years in a nationally representative US survey answered questions about receipt of at least one dose of HPV vaccine. Unvaccinated women were asked about their intent to get vaccinated in the next 12 months. Demographic and sexual behaviour correlates were evaluated in bivariate and multivariable analyses by age for (a) receipt of HPV vaccine and (b) intention to receive HPV vaccine. Results: Overall, 23.1% of respondents reported receiving HPV vaccine; significantly more 15–19 year olds were vaccinated compared to 20–24 year olds (30.3% vs 15.9%, p<0.001). There was no difference in receipt of vaccine by race/ethnicity for 15–19 year olds, but 20–24 year old non-Hispanic blacks were less likely than non-Hispanic whites to have received vaccine [aOR=0.2 (0.1, 0.4)]. Women who had insurance were more likely to have received HPV vaccine. HPV vaccination was not associated with being sexually active or lifetime number of sex partners. Among sexually active 15–19 year olds, those who received HPV vaccine were more likely to report always wearing a condom [aOR=3.0 (1.1, 7.9)] than those who had not received vaccine. A majority of unvaccinated women in both age groups are not likely to get vaccinated in the next 12 months (62% of 15–19 year olds and 58.0% of 20–24 year olds). Sexually active women were more likely to intend to get vaccinated [15–19 year olds: aOR=2.6 (1.2, 5.5); 20–24 year olds: aOR=2.2 (1.1, 4.3)]. Conclusions: These nationally representative data from the US highlight disparities in HPV vaccine uptake by insurance status among 15–24 year old women and by race/ethnicity among women above age 19. Our data do not suggest that HPV vaccination results in more sexually-risky behaviour, however, further data on timing of vaccination and sexual initiation are needed. Continued efforts are needed to encourage vaccination before initiation of sexual activity when the benefit of vaccination would be greatest.